Araneibatrus phuphaphet sp. nov., a new cavernicolous Pselaphinae from Satun Geopark, southern Thailand (Coleoptera: Staphylinidae: Pselaphinae) - Yin, Zi-Wei; Jantarit, Sopark (Zootaxa, 2019)
A new cavernicolous species of the genus Araneibatrus Yin & Li, 2010, A. phuphaphet sp. nov., is described from Phu Pha Phet Cave, Satun Province, southern Thailand. The discovery extends the known distributional range of Araneibatrus for more than 1,500 km southwards. The conspicuously spinose pronotum, sexually modified profemur of the male, and unique configuration of the aedeagus serve to readily separate the new species from all known congeners.